2019
DOI: 10.1186/s12876-019-1121-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, benefit harm and cost effectiveness of colorectal cancer screening in Austria

Abstract: Background: Clear evidence on the benefit-harm balance and cost effectiveness of population-based screening for colorectal cancer (CRC) is missing. We aim to systematically evaluate the long-term effectiveness, harms and cost effectiveness of different organized CRC screening strategies in Austria. Methods: A decision-analytic cohort simulation model for colorectal adenoma and cancer with a lifelong time horizon was developed, calibrated to the Austrian epidemiological setting and validated against observed da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…The screening methods considered in these studies were iFOBT (70%), colonoscopy (67%), gFOBT (42%), and sigmoidoscopy (30%), but they were not conclusive on which screening method is the best to adopt for population-based CRC screening programs [78]. While the study by Jahn et al [79] concluded that the most effective CRC screening method was iFOBT annually or colonoscopy every 10 years, the gFOBT was less effective and more expensive than the iFOBT. Colonoscopy was found to be cost-effective compared to no screening, and an ICER of 15,000 EUR per LY was obtained when colonoscopy was switched with the iFOBT [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The screening methods considered in these studies were iFOBT (70%), colonoscopy (67%), gFOBT (42%), and sigmoidoscopy (30%), but they were not conclusive on which screening method is the best to adopt for population-based CRC screening programs [78]. While the study by Jahn et al [79] concluded that the most effective CRC screening method was iFOBT annually or colonoscopy every 10 years, the gFOBT was less effective and more expensive than the iFOBT. Colonoscopy was found to be cost-effective compared to no screening, and an ICER of 15,000 EUR per LY was obtained when colonoscopy was switched with the iFOBT [79].…”
Section: Discussionmentioning
confidence: 99%
“…While the study by Jahn et al [79] concluded that the most effective CRC screening method was iFOBT annually or colonoscopy every 10 years, the gFOBT was less effective and more expensive than the iFOBT. Colonoscopy was found to be cost-effective compared to no screening, and an ICER of 15,000 EUR per LY was obtained when colonoscopy was switched with the iFOBT [79]. A cost-benefit analysis study by Heavener et al [80] also showed that CRC screening gives great returns; however, health systems need to construct payment models to provide better incentives to health providers who implement CRC screening [81].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endoscopists performing the procedure should have fulfilled minimum training benchmarks as found in the US when screening patients ≥ 50 years of age [42]. Overall, a review study discussing the use of colonoscopy in the detection of CRC described 94.7% sensitivity across 49 studies encompassing 11,151 patients [43].…”
Section: Screening Tests In Brief: Positives and Negativesmentioning
confidence: 99%
“…The most informative empirical data emerge from the observation of rising incidence in multiple high resource nations but a different trend in Austria. Austria has instituted opportunistic screening at age 40, and as a result, colorectal cancer incidence is rising in individuals up until age 39 but declining in those 40 and over 11 …”
Section: Criticisms Of the Recommended Change In Age To Start Screeningmentioning
confidence: 99%